SOBRE EL PARASITISMO DEL EOXENOS LABOULBENEIPEYER INS STREPS - PIELTAIN BOLIVAR, C (Universidad Nacional Autónoma de Mexico, Escuela de Medicina, CD MEXICO, DF, MEX, 1950)
Occurrence of this sp in bat guano in a cave at Tuxtla Gutierrez, Chiapas is descr It did not parasitize the bats 3 references
CIENC MEX
Keywords: PARASITISMO, EOXENOS LABOUL BENEIPEYER, INS STREPS; MULTIDISCIPLINARIA; MICROBIOLOGIA; BACTERIOLOGIA